Amplified Emissions Spectroscopy for Sensing Applications. Issue 11 (20th September 2019) - Sun, Tao; Du, Zhenhui; Li, Jinyi; Ma, Yiwen
Abstract: Amplified emission spectroscopy is promising for applications of qualitative and quantitative sensing of elements and their states. This technique has the characteristics of a narrow spectral line, high spectral resolution, and high signal‐to‐noise ratio. Recently, this technology has advanced tremendously with progress in excitation methods, that is, resonance multiphoton absorption and filamentation with ultrafast lasers. The mechanism, conditions, excitation, signal processing, and applications of amplified emission spectroscopy are reviewed herein. In particular, the different formation patterns of the amplified emission spectra produced by an ultrafast laser are analyzed in detail. In addition, a brief introduction is given to the existing applications of amplified emission. Finally, both a conclusion and a perspective of the future for amplified emission are presented. Abstract : Amplified emission spectroscopy as a new promising method in sensing application field is rapidly evolving. With the development of ultra‐fast femtosecond laser technology, more and more spectroscopy scientists are paying great attention to this technology, which makes it possible to detect short‐lived trace substances in chemical reaction processes with high sensitivity, and to understand the fine emissions spectrum.